SEVERITY OF BRONCHIAL ASTHMA AMONG SCHOOL CHILDREN IN JAZAN REGION, SAUDI ARABIA: Pharmaceutical Science-Medicine - BASUDAN, ABDULHAMEED; MOAFA, ABDULRAHMAN; FAQIHI, MOHAMMED; ALHAZMI, MOHAMMED; MAHNASHI, TAHER; KHAWAJI, ALHUSSEN; HADDADI, YASEEN; YASSIN, ABUOBAIDA (International Journal of Life Science and Pharma Research, 2019)
Asthma is a worldwide health problem; its prevalence varies among different countries and cities and age groups. In children asthma is one of the most common chronic diseases and leading causes of morbidity. This study is aimed at identifying important risk factors associated with the severity of bronchial asthma among school children in Jazan region. This cross-sectional study was made using the International Study of Asthma and Allergies in Children (ISAAC) questionnaire. The study surveyed 1505 school children from different geographical areas in Jazan region using multistage cluster sampling technique. The descriptive statistics of the demographics and asthma severity variables were calculated using frequencies, percentages, and tables. The total study population was 1400, most of them were Saudi Arabians (1273-90.9%). The frequency of disturbed sleep at night due to wheezing or breathing problems was 111 (7.9%) in the included students. Nocturnal cough was reported in 332 (23.7%) of participants and 280 (20.0%) of them had wheeze resulting in limitation of speech. Frequency of urgent visits to doctor/emergency department (ED) due to wheezing or breathing problems was reported in 159 (11.4%) with clear statistically significant difference in frequency between male and female (p=0.023). Rate of hospital admission due to wheezing or breathing problems was 89 (6.3%).